Assessing the Impact of COVID-19 on Pregnancy and Maternal Outcomes: A Slovak National Study - Adriána Goldbergerová; Ladislav Kováč; Cecília Marčišová; Miroslav Borovský; Dominika Kotríková; Ľubomíra Izáková; Ján Mikas; Jana Námešná; Zuzana Krištúfková; Alexandra Krištúfková (Reproductive Medicine)
Background: The COVID-19 pandemic highlighted the global challenge of inadequate data on SARS-CoV-2’s effects on pregnant women and their infants. In response, Slovakia, along with other countries, launched a nationwide study to assess the incidence, characteristics, and outcomes of SARS-CoV-2 infection during pregnancy. Methods: We conducted a national observational descriptive study of SARS-CoV-2 positive cases among pregnant women from the pandemic’s onset to its conclusion. In collaboration with the Public Health Office of the Slovak Republic, we identified 1184 pregnant women who tested positive for SARS-CoV-2 and contacted them for participation. Results: Among the 240 participating SARS-CoV-2-positive pregnant women, 13 required hospitalizations, with an increased need for intensive care and respiratory support. However, the absolute risk of poor outcomes remained low. Higher maternal age and infection during the third trimester emerged as key risk factors for hospitalization. A symptomatic course was dominant, with fatigue (70%), headache (58%), and fever (56%) as the leading symptoms. While maternal and neonatal outcomes were generally favourable, a slight increase in caesarean sections and preterm births suggests an indirect impact on maternity care. Vaccination during pregnancy correlated with reduced symptoms and no hospitalizations. Elevated CRP levels were common among infected women, while ultrasound findings remained normal. Conclusions: This study offers a multi-dimensional view of pregnancy during the pandemic, capturing both the mother’s personal concerns and the objective insights from prenatal and labour care settings. The findings suggest that most pregnant women with SARS-CoV-2 experience mild to moderate illness, offering reassurance to clinicians about generally favourable maternal and neonatal outcomes while underscoring the need for vigilance in rare severe cases.